Effect of nitrogen addition on morphology and magnetic properties of electrodeposited Co-Ni granular films - Sirbu, C; Georgescu, V (Journal of Optoelectronics and Advanced Materials, 2008)
The granular films of magnetic alloys consisting of nanoscale ferromagnetic particles which exhibit a giant magnetoresistance (GMR) effect have been a subject of great interest in recent years. In this work, we report on experimental investigation of the influence of nitrogen addition on magnetic and transport properties of Co-Ni granular films with different nitrogen content, and on the surface morphology. The correlation between these properties and the electrodeposition conditions has been studied. The granular thin films were electrodeposited onto a disk-shaped aluminium substrate, from a basic bath containing: CoSO4.7 H2O, NiSO4.7 H2O, and NiCl2.6H2O with 20 0-1 total metallic ion content. As additional substances were used NaCl, Na2SO4.10 H2O, H3BO3, sodium citrate, sodium laurylsulphate, sodium saccharine and NaNO3 as a source for nitrogen inclusion in the films. The concentration of NaNO3 in electrolytic bath was varied with the aim to control the films nitrogen content. Co-Ni-N granular films display GMR effect of about 60%; this could be explained mainly by the elastic spin dependent scattering of conduction electrons at the interface between magnetic (CoNi solid solution grains) and nonmagnetic regions (rich in N inter-granular frontiers and aluminium oxidized substrate).